The nanotechnology revolution in Barcelona: innovation & creativity by universities - Juanola-Feliu, Esteve (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2009)
AbstractThis paper analyses the state of the art for nanotechnology in Barcelona, focussing on the scientific and economic challenges arising from nanotechnologies and the creative and innovative framework in Barcelona that could be used to meet them. Nanotechnology is an endless source of innovation and creativity at the intersection of medicine, biotechnology, engineering, physical sciences and information technology, and it is opening up new directions in R + D, knowledge management and technology transfer. Given the huge economic investment and cutting-edge research in the field of nanotechnology, a creatively managed and cooperation-based university industry is more in demand than ever before.